Representation of hybridity in the main character of Sindhunata’s Novel Putri Cina - Alfiyah; Iswatiningsih, Daroe; Sunaryo, Hari; Sugiarti (Universitas Muhammadiyah Malang, 2024)
Minority and colonialism among ethnic Chinese have been growing for a long time in Java. This is a manifestation of colonialism that resulted from the invaders. This research aims to reveal the depiction of minorities and colonialism regarding the existence of ethnic Chinese in the novel Putri Cina by Sindhunata by employing a qualitative method with a hybrid approach. The data for this research are quotes of words, sentences, paragraphs, or discourse that show the presence of elements of hybridity in the novel Putri Cina by Sindhunata. The data collection technique in the research is by (1) reading in depth and repeatedly the novel Putri Cina by Sindhunata, (2) determining the elements of the hybridity approach, (3) paying close attention to every word, sentence, paragraph, or discourse that shows the existence of elements of hybridity, and (4) noting down words, sentences, paragraphs or discourse that show elements of hybridity. Data analysis uses qualitative techniques with hybridity studies. The research results show the existence of hybridity and ambivalence. In the study of hybridity, four types of hybridity were found, namely (1) dual identity, (2) intermarriage, (3) wayang potehi and cucak rowo song, and (4) arak-drinking culture.